Development of a narrow-directional social network for fans of TV series - K. I. Frolov (E-Management)
It often happens that a social network of a general orientation is not convenient for a specifc group of people due to the specifcs of their interests. The community of TV series fans is one of these groups. Therefore, the development of a narrowly focused social network, which will implement functionality for a certain category of users, is very relevant. The purpose of this work is to develop an information system, which is a narrowly focused social network for fans of TV shows with functionality that meets the needs of this group of people, taking into account the specifcs of their interests. Main tasks: determination of user needs; analysis of the functionality of existing solutions and identifcation of components that need to be  implemented; study of approaches to the design of recommender systems; choice of means and methods of development; system design and development. As a result, an information system that can satisfy the needs of series lovers was designed. The developed system provides a functionality that allows user to keep track of watched episodes, get fresh and up-to-date information about TV shows, discuss news and TV shows with other people, receive personal recommendations, etc. At the same time, users can access the system using various types of devices: smartphones or tablets running iOS and Android operating systems, desktop computers and laptops.